Stabilisasi Tanah Lempung Dengan Penambahan Limbah Gypsum Ditinjau Dari Nilai Kuat Geser - Fitridawati Soehardi; M. Yusuf Septino; Zainuri Zainuri (SAINSTEK, 2023)
Indonesia has clay land that mostly fills its territory One of these parts of the area is Riau Province. The location of Riau Province which is on the coast and lowlands causes its area to be poor clay soil. Many types of soils with low carrying capacity can be found in banguanan construction, one of which is clay soil. Loamy soils are known to have the property of becoming hard when dry, becoming soft, when wet, with a very large change in size depending on the presence of water. From this explanation, clay soil is not good for infrastructure development on clay soil, so improvements are needed by means of soil stabilization. Soil stabilization is an attempt to change or improve the technical properties of the soil such as: carrying capacity, compressibility, permeability, development potential and sensitivity to changes in moisture content in order to meet certain technical requirements, by adding certain materials to the soil. The purpose of soil stabilization is to increase the carrying capacity of the soil by increasing soil parameters such as, density, shear strength and so on. Direct Shear Test Method This examination is carried out to determine the cohesion values (c) and shear angle (o) of the soil. The results showed that in the addition of a mixture of gypsum waste with levels of 0%, 8%, 10% and 12% the value of direct shear strength (S) increased at a percentage of 12%, namely 0,6826 kg/cm2 compared to the value of direct shear strength on the original soil of 0,5371 kg/cm2, there was an increase of 27,08%. This increase occurs because gypsum contains calcium which binds organic material soils to clay. Gypsum also absorbs more water, making the mixture of waste and soil samples become harder and stronger.